Zero war - Gage, Christos; Mustard, Donald (Fortnite X Marvel, 2022)
"The Marvel Universe collides with video game phenomenon Fortnite! The inhabitants of the Island are locked in a neverending war, and only one thing has the potential to turn the tide -- a crystallized fragment of the Zero Point that was cast into the Marvel Universe! Spider-Man, Wolverine and Shuri must team with several Fortnite fighters to hunt down the elusive Zero Shard. Can these allies find it in time and avert catastrophe? And can the heroes of the Marvel and Fortnite realities hold off the Imagined Order long enough to give them a fighting chance? Epic Games' Chief Creative Officer, Donald Mustard, teams up with veteran Marvel writer Christos Gage (SPIDER-GEDDON, AVENGERS ACADEMY) and artist Sergio Dávila (CAPTAIN MARVEL) for a blockbuster crossover event with enormous ramifications for both universes!"--Amazon.com.